A single night of sleep loss impairs objective but not subjective working memory performance in a sex‐dependent manner. (31st January 2018) - Rångtell, Frida H.; Karamchedu, Swathy; Andersson, Peter; Liethof, Lisanne; Olaya Búcaro, Marcela; Lampola, Lauri; Schiöth, Helgi B.; Cedernaes, Jonathan; Benedict, Christian
Summary: Acute sleep deprivation can lead to judgement errors and thereby increases the risk of accidents, possibly due to an impaired working memory. However, whether the adverse effects of acute sleep loss on working memory are modulated by auditory distraction in women and men are not known. Additionally, it is unknown whether sleep loss alters the way in which men and women perceive their working memory performance. Thus, 24 young adults (12 women using oral contraceptives at the time of investigation) participated in two experimental conditions: nocturnal sleep (scheduled between 22:30 and 06:30 hours) versus one night of total sleep loss. Participants were administered a digital working memory test in which eight‐digit sequences were learned and retrieved in the morning after each condition. Learning of digital sequences was accompanied by either silence or auditory distraction (equal distribution among trials). After sequence retrieval, each trial ended with a question regarding how certain participants were of the correctness of their response, as a self‐estimate of working memory performance. We found that sleep loss impaired objective but not self‐estimated working memory performance in women. In contrast, both measures remained unaffected by sleep loss in men. Auditory distraction impaired working memory performance, without modulation by sleep loss or sex. Being unaware of cognitive limitations when sleep‐deprived, as seen in our study, could lead to undesirable consequences in, for example, an occupational context. Our findings suggest that sleep‐deprived young women are at particular risk for overestimating their working memory performance.